Evaluation of Deep Choroidal Vascular Changes Using Enface Oct in Central Serous Choroidopathy - Hasan, Nasiq; Chawla, Rohan; Kumar, Prashant; Sundar, Dheepak; Raj, Nimmy (Asian Journal of Medical Research, 2021)
Background: To detect changes in deep choroidal vasculature following resolution of CSC using Enface SSOCT. Subjects and Methods: Nine eyes of patients with CSC were studied during the acute phase and following resolution. OCT-A scans were obtained and the deep choroidal layer was segmented between 150 to 300 microns below the RPE. The dilated deep choroidal vessels visible on EnFace OCT corresponding to the leak on FA were localized and the area and width of the vessel was compared using imageJ software. Other parameters like best corrected visual acuity and central choroidal thickness was also measured and compared before and after resolution of CSC. Results: Mean age of the patients was 41.22 7.45 years. There was a significant decrease in width (0.89 0.48mm vs 0.662 0.27mm, p=0.007) and area (0.81 0.61mm2 vs 0.56 0.46mm2,p=0.009) of the dilated vessel post resolution of CSC ) however the overall decrease in choroidal thickness from 428.22 73.11 to 419 69.77 microns was not significant. (p=0.365). Conclusion: EnFace SSOCT scans can be used as a tool to identify anatomical changes in the deep choroidal vessels during the course of the disease and to help monitor the response of treatment in CSC